2003
DOI: 10.2214/ajr.181.6.1811519
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy Chest Radiography with a Flat-Panel Digital Detector: Revealing Calcified Chest Abnormalities

Abstract: Dual-energy images added to standard posteroanterior chest radiographs significantly improve the detection of calcified chest lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 18 publications
0
53
0
4
Order By: Relevance
“…Previous studies have suggested potential improvements for the detection of non-calicified as well as calcified lung nodules by cesium-iodide (CsI) detector-based dualexposure dual-energy chest radiography compared to standard chest radiography alone [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested potential improvements for the detection of non-calicified as well as calcified lung nodules by cesium-iodide (CsI) detector-based dualexposure dual-energy chest radiography compared to standard chest radiography alone [3].…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, the literature mostly has documented the better detection of calcified pulmonary nodules using the dual exposure technique or older single-shot exposure systems [6][7][8][9][10][11][12][13][14]. The latter, despite promising initial results, fell into disfavor because of their cumbersome handling and inconsistent image quality.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, computer-aided detection (CAD) techniques have been developed for chest radiography, analogous to those used with chest CT, to aid in the detection of lung nodules. Studies have analyzed the diagnostic gain from bone subtraction or suppression and CAD separately [7][8][9][10][11][12][13] Z. Szucs-Farkas received fees from the Riverain Technologies Group for collecting anonymized patient data for a different reader study. That study is not related to the current investigation in any way.…”
mentioning
confidence: 99%